Halliday / Resnick fundamentals of physics - Halliday, David 1916-2010; Resnick, Robert 1923-; Walker, Jearl 1945- (John Wiley & Sons, Inc., 2008)
Offers an understanding of the fundamental physics concepts, and helps readers apply this conceptual understanding to quantitative problem solving. This book offers a combination of authoritative content and stimulating applications.